The stable hydrogen isotopic composition of sedimentary plant waxes as quantitative proxy for rainfall in the West African Sahel. (1st July 2016) - Niedermeyer, Eva M.; Forrest, Matthew; Beckmann, Britta; Sessions, Alex L.; Mulch, Andreas; Schefuß, Enno
Abstract: Various studies have demonstrated that the stable hydrogen isotopic composition (δD) of terrestrial leaf waxes tracks that of precipitation (δDprecip ) both spatially across climate gradients and over a range of different timescales. Yet, reconstructed estimates of δDprecip and corresponding rainfall typically remain largely qualitative, due mainly to uncertainties in plant ecosystem net fractionation, relative humidity, and the stability of the amount effect through time. Here we present δD values of the C31 n -alkane (δDwax ) from a marine sediment core offshore the Northwest (NW) African Sahel covering the past 100 years and overlapping with the instrumental record of rainfall. We use this record to investigate whether accurate, quantitative estimates of past rainfall can be derived from our δDwax time series. We infer the composition of vegetation (C3 /C4 ) within the continental catchment area by analysis of the stable carbon isotopic composition of the same compounds (δ 13 Cwax ), calculated a net ecosystem fractionation factor, and corrected the δDwax time series accordingly to derive δDprecip . Using the present-day relationship between δDprecip and the amount of precipitation in the tropics, we derive quantitative estimates of past precipitation amounts. Our data show that (a) vegetation composition can be inferred from δ 13 Cwax, (b) the calculated net ecosystem fractionation represents a reasonable estimate, and (c) estimated total amounts of rainfall based on δDwax correspond to instrumental records of rainfall. Our study has important implications for future studies aiming to reconstruct rainfall based on δDwax ; the combined data presented here demonstrate that it is feasible to infer absolute rainfall amounts from sedimentary δDwax in tandem with δ 13 Cwax in specific depositional settings.